1988
DOI: 10.3168/jds.s0022-0302(88)79539-9
|View full text |Cite
|
Sign up to set email alerts
|

Lactational Response to Soybean Meal, Heated Soybean Meal, and Extruded Soybeans with Ruminally Protected Methionine

Abstract: Seventy-three high producing Holstein cows were arranged in a 3 X 2 factorial to evaluate three protein supplements (soybean meal, heat-treated soybean meal, and extruded blend of soybeans and soybean meal) without or with 15 g/head/d of ruminally protected DL-methionine during wk 4 through 16 postpartum. Total mixed diets contained (DM basis) 30% corn silage, 15% alfalfa hay, and 55% of the respective concentrate mix. Milk production was higher when cows were fed either heated soybean product instead of soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
8

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 23 publications
2
23
1
8
Order By: Relevance
“…In line with our results, Mielke and Schingoethe (1981) reported no response in milk production of cows fed heat treated soybeans. Schingoethe et al (1988) reported a depression of milk fat for dairy cows fed heated soybeans whereas Faldet and Satter (1991) and our study showed that milk fat percentage was similar among treatments. Fat yield was higher for the heated soybean diet in the study by Faldet and Satter (1991) whereas no effect on fat yield was detected in our study among different diets.…”
Section: Effect On Milk Productionmentioning
confidence: 41%
“…In line with our results, Mielke and Schingoethe (1981) reported no response in milk production of cows fed heat treated soybeans. Schingoethe et al (1988) reported a depression of milk fat for dairy cows fed heated soybeans whereas Faldet and Satter (1991) and our study showed that milk fat percentage was similar among treatments. Fat yield was higher for the heated soybean diet in the study by Faldet and Satter (1991) whereas no effect on fat yield was detected in our study among different diets.…”
Section: Effect On Milk Productionmentioning
confidence: 41%
“…According to a review by Santos et al (1998), the literature does not give a consistent picture of the effect of heat treatment of supplement feed on milk production. Studies by Netemeyer et al (1982), Forster et al (1983, Schingoethe et al (1988), Faldet and Satter (1991), Tuori (1992) and Bertilsson et al (1994) showed increased milk production after heat treatment of the supplement feed. Several other experiments found very small or no effect of heat treatment of supplement (Ahrar and Schingoethe, 1979;Mielke and Schingoethe, 1981;Annexstad et al, 1987;Bernard, 1990;Framstad et al, 1991;Tuori, 1992;McNiven et al, 1995;Huhtanen and Heikkilä, 1996;Pires et al, 1996;Henriksen, 1999;Rinne et al, 1999).…”
Section: Milk Productionmentioning
confidence: 95%
“…Mean and median values were similar for all variables in this data set. A significant curvilinear relationship (R 2 = 0.19) was found between milk yield and the concentration of CP All data were taken or calculated from experiments reported in 112 independent studies (Barney et al, 1981;Mielke and Schingoethe, 1981;van Dijk et al, 1983;Henderson et al, 1985;Polan et al, 1985Polan et al, , 1997Van Horn et al, 1985;Broderick, 1986Broderick, , 1992Broderick, , 2003Lundquist et al, 1986;Annexstad et al, 1987;Garnsworthy and Jones, 1987;Howard et al, 1987;Jaquette et al, 1987;Kaim et al, 1987;Bowman et al, 1988;Hadsell and Sommerfeldt, 1988;Jones and Garnsworthy, 1988;Léonard and Block, 1988;Manson and Leaver, 1988;Robinson and Kennelly, 1988;Schingoethe et al, 1988;Sloan and Rowlinson, 1988;Voss et al, 1988;Bruckental et al, 1989Bruckental et al, , 2000De Gracia et al, 1989;Garnsworthy, 1989;Herrera-Saldana and Huber, 1989;Higginbotham et al, 1989;Mä ntysaari et al, 1989;Blauwiekel et al, 1990;Broderick et al, 1990Broderick et al, , 1993Canfield et al, 1990;Casper et al, 1990Casper et al, , 1999…”
Section: Performance Of Lactating Dairy Cowsmentioning
confidence: 99%